NIKOLAI KONSTANTINOVICH KOL’TSOV, THE AUTHOR OF THE TEMPLATE-DIRECTED SYNTHESIS CONCEPT AND FOUNDER OF EXPERIMENTAL BIOLOGY IN RUSSIA - N. N. Yurchenko; O. V. Trapezov; I. K. Zakharov (Вавиловский журнал генетики и селекции)
Nikolai K. Kol’tsov (1872–1940) went on his scientific way from comparative anatomy of vertebrates to experimental cytology and then to genetics and molecular biology. He discovered the cytoskeleton. He foresaw that the successful development in biology would require a union with physics, chemistry, and mathematics. He demonstrated that strong physical and chemical factors could produce mutations in organisms. He also put forward the concept of template-directed synthesis of biopolymers. Professor Kol’tsov established a prominent school of experimental biologists, who succeeded in studies of special genetics of animals and plants, artificial mutagenesis, population genetics, and other fields. For four decades Koltsov was working on one major problem, cell organization. His studies were in line with trends in global biology. He participated in the creation and development of new experimental approaches in cytology, biochemistry, developmental mechanics, and genetics.